Crosstalk Between Type VI Secretion System and Mobile Genetic Elements - Peñil-Celis, Arancha; Garcillán-Barcia, M. Pilar (Frontiers in Molecular Biosciences, 2019)
Many bacterial processes require cell-cell contacts. Such are the cases of bacterial conjugation, one of the main horizontal gene transfer mechanisms that physically spreads DNA, and the type VI secretion systems (T6SSs), which deploy antibacterial activity. Bacteria depend on conjugation to adapt to changing environments, while T6SS killing activity could pose a threat to mating partners. Here we review the experimental evidences of overlapping and interaction between the T6SSs, bacterial conjugation and conjugative genetic elements.